Mindfulness-based cognitive therapy for depression in people with dementia: A qualitative study on participant, carer and facilitator experiences. (February 2022) - Douglas, Sarah; Stott, Josh; Spector, Aimee; Brede, Janina; Hanratty, Éanna; Charlesworth, Georgina; Noone, Deirdre; Payne, Jacob; Patel, Mina; Aguirre, Elisa
Background: Depression in dementia is common and associated with negative health outcomes. Mindfulness-based cognitive therapy is a recommended treatment of choice for recurrent depression, but its use for depression in dementia is yet to be assessed. Objective: This study aimed to investigate the experiences of people with depression and dementia who participated in the mindfulness-based cognitive therapy intervention and those of their carers and facilitators. Methods: This qualitative study was nested within a randomised controlled feasibility study. Semi-structured interviews were conducted with 18 people (eight people with dementia and depression, six carers and four course facilitators). Thematic analysis was used to analyse the data. Findings: Several beneficial effects of mindfulness-based cognitive therapy were described. These were a sense of shared suffering among the group, greater present moment focus and awareness, various positive emotional changes, including greater self-compassion, and benefits for carers, such as the reduction of anxiety. Specific aspects of the programme were identified as particularly useful, including facilitator characteristics and certain mindfulness practices. Carer involvement, cognitive difficulties and barriers to home practice influenced engagement with the course. Facilitators described adaptations made to mindfulness-based cognitive therapy and suggested additional modifications for future groups. Conclusion: Results of this process evaluation suggest that mindfulness-based cognitive therapy is a potentially useful intervention for people with depression in dementia, but that further adaptation of the intervention is required to make the programme suitable for this clinical population.